Pengaruh Pembiayaan Umkm Dan Modal Terhadap Laba Pada Koperasi Sriwijaya Pariaman - Oktaviani, Nichy; Sudirman, Sudirman (CV. ITTC INDONESIA, 2021)
This study aims to determine the effect of MSME Medium Financing and Capital on Profit at the Sriwijaya Pariaman Cooperative in 2016-2020 partially and simultaneously. This research was conducted at the Sriwijaya Savings and Loans Cooperative, Pariaman City using secondary data, with multiple linear analysis techniques. Based on the partial results (T test) of the Micro, Small and Medium Enterprises (MSME) Financing variable, the value of Sig. from the results of the T test of 0.000, it is smaller than the value of 0.05 (0.000 < 0.05) and the Modal variable with the value of Sig. From the results of the T test of 0.009, it is smaller than the value of 0.05 (0.009 <0.05), which means that partially the two variables have a significant positive effect on the Profit of the Sriwijaya Pariaman Cooperative, while simultaneously (F test) Financing for Micro, Small and Medium Enterprises and Capital Adequacy with a significance value of 0.006 less than 0.05 (0.006 < 0.05) which means it has a significant effect simultaneously on the Profit of the Sriwijaya Pariaman Cooperative. The coefficient of determination of the R Square value is 0.570, this shows that 57% of the Sriwijaya Cooperative Profit in Pariaman City is influenced by the variation of the two independent variables used, namely MSME Financing (X1) and Capital (X2). While the remaining 43% are influenced outside this variable.